Foliar anatomy of Cynoglossum L. (Boraginaceae) from north Anatolia, Turkey - Akçin, Öznur Ergen; Çoskunçelebi, Kamil; Senel, Gülcan (Bangladesh Journal of Plant Taxonomy, 2012)
Bracts, basal and cauline leaves of North Anatolian representatives of Cynoglossum, viz., C. creticum Miller, C. officinale L., C. montanum L. and C. glochidiatum Wall. were investigated anatomically. Foliar thickness, trichome length and types, stomata types, stomata index, the presence of collenchyma and sclerenchyma were found to be important for delimitation of Cynoglossum species. All examined species have isobilateral leaf. Stomata were anisocytic and anomocytic. All the studied species had trichomes. Simple long and short trichomes were seen in leaves of C. creticum. Long and short trichomes with cystoliths at the base were seen in all leaves of C. montanum. Unicellular and multicellular unbranched trichomes and glandular trichomes were found in leaves of C. officinale. Short and adpressed trichomes were seen in leaves of C. glochidiatum.